ChemInform Abstract: Sodium Nitrite‐Catalyzed Aerobic Oxidative Csp2—Csp3 Coupling: Direct Construction of the 4‐Aryldihydroisoquinolinone Moiety. Issue 35 (2nd September 2014) - Su, Bo; Deng, Meng; Wang, Qingmin
Abstract A facile protocol using NaNO2 as the catalyst and air as the terminal oxidant enables the synthesis of the title species via direct oxidative intramolecular coupling.